Praktik Pemberdayaan UMKM melalui Inovasi Produk dan Pemasaran Berbasis Digital untuk Meningkatkan Pendapatan Masyarakat Desa Saringembat - M. Zidhan Nurul Huda; Maharani Ikaningtyas (Lembaga Pengembangan Kinerja Dosen, 2025)
Saringembat Village has a variety of local products with significant potential; however, the marketing and management of these products remain limited. This program aims to assist MSME actors in leveraging digital technology to develop products, expand markets, and enhance competitiveness. Through training and mentoring, participants were taught product innovation, packaging design, logo creation, and the application of digital marketing through platforms such as social media and marketplaces. The results of this activity indicate that the utilization of digitalization can increase market reach and product sales volume, although challenges related to digital literacy and resource limitations still need to be addressed. This research highlights the importance of utilizing digital technology to empower MSMEs and sustainably improve the village economy.